The collected writings of John Maynard Keynes, Volume 10, Essays in biography - Keynes, John Maynard 1883-1946 (The collected writings of John Maynard Keynes, 2013)
Most of the essays in this book were first collected and published in 1933, when Keynes had reached a turning point in a highly successful career as an academic economist, as an official economic advisor, opponent of the reparation imposed on Germany and critic of the orthodox economic policies of British governments. Before devoting himself fully to the final stages of his journey towards The General Theory, Keynes put together these examples of one of his favourite literary genres, the psychological portrait and biographical sketch. With the additions made in 1951 and 1972, the book contains almost all of Keynes's biographical writings: his savage portraits of the architects of the Treaty of Versailles and sketches of other politicians, including Asquith and Churchill; some classic accounts of the lives of economists; a pair of autobiographical memoirs; a short study of Newton; and many acute and affectionate character sketches of friends